2017
DOI: 10.1016/j.bbr.2017.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and dopamine receptor D1 associated with decreased social interaction

Abstract: Deficits in social interaction are hallmarks of neurological and psychiatric disorders. However, its underlying mechanism is still unclear. Here, we show that the loss of dendritic cell factor 1 (Dcf1) in the nervous system of mice induces social interaction deficiency, autism-like behaviour, and influences social interaction via the dopamine system. Dopamine receptor D1 agonist rescues this social cognition phenotype, and improves short-term plasticity. Together, this study presents a new genetic mechanism th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In line with our results, changes in hippocampal dopamine and D1 receptor levels associated with social deficits have been demonstrated in a genetic mouse model exhibiting autism-relevant behavioral abnormalities (Liu et al, 2017). Furthermore, mice knockout for genes strongly associated with ASD, such as Cntnap4 (Karayannis et al, 2014) and neuroligin-3 (Rothwell et al, 2014) mutant mice, show changes in NAc dopaminergic neurotransmission together with deficits in the core ASD behavioral domains.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, changes in hippocampal dopamine and D1 receptor levels associated with social deficits have been demonstrated in a genetic mouse model exhibiting autism-relevant behavioral abnormalities (Liu et al, 2017). Furthermore, mice knockout for genes strongly associated with ASD, such as Cntnap4 (Karayannis et al, 2014) and neuroligin-3 (Rothwell et al, 2014) mutant mice, show changes in NAc dopaminergic neurotransmission together with deficits in the core ASD behavioral domains.…”
Section: Discussionsupporting
confidence: 92%
“…Social interaction was found compromised in a rat model where D1Rs are mutated in a way that insertion of the receptors is less likely in the neuronal membranes [252]. In another genetic mouse model of ASD, impaired social behavior was normalized by treatment with the selective D1R agonist SKF38393 [253].…”
Section: Indirect Effect Through D1rmentioning
confidence: 99%
“…Many neuropsychiatric disorders share both DAergic and developmental hypotheses (Howes & Kapur, ; Lawford et al, ; Liu, Shi, Lin, & Wen, ; Madras, Miller, & Fischman, ; Souza et al, ). In our previous study, we showed that zebrafish larvae treated with DA in the 3 to 5 dpf developmental window presented a lower number of mobile episodes at 5 dpf (Souza et al, ).…”
Section: Resultsmentioning
confidence: 99%